(untitled) (European Journal of Behavioral Sciences, 2025)
As the fashion industry grows, so does the demand for second-hand clothes. This study investigates the perceptions of different generations toward second-hand clothing and explores the factors influencing their purchasing decisions. Using a quantitative survey, the data were collected from 83 individuals classified as Generation Z, Millennials, and Generation X, based in India. Standardized questions were included in the survey to evaluate the key determinants of customer buying behavior, such as product features, price sensitivity, status symbol, location, and emotions and experiences. The data was analyzed using graphs and statistical tests such as Levene’s and independent T-tests. From the results, it was found that product features were the only factor that showed a significant generational difference, implying that while purchasing second-hand clothes, Generation Z and Millennials are highly influenced by the features of the product, as compared to Generation X. Conversely, price sensitivity, status symbol, location, and emotions and experiences impacted all the generations similarly. Moreover, while second-hand fashion has been increasing recently, some important features, like affordability, current fashion trends, and easy accessibility to e-commerce and marketplaces, attract all generations. However, the discouraging factors, including hygiene concerns, low quality, stigma, negative energy, superstition, and time-consuming processes, contributed to the slow growth of this industry. Among these barriers, hygiene concerns and a time-consuming process are highly influential, followed by low quality and stigma in all generations. These insights provide businesses and policymakers with valuable guidance to enhance marketing strategies and product offerings, ultimately promoting sustainable fashion consumption across generations.